Revision Total Hip Arthroplasty after Ceramic Bearing Fractures in Patients Under 60-years Old; Mid-term Results - Im, Chulsoon; Lee, Kyung-Jae; Min, Byung-Woo; Bae, Ki-Cheor; Lee, Si-Wook; Sohn, Hyuk-Joon (Hip & pelvis, 2018)
Although advances in technology have reduced the risk of ceramic implant fractures in total hip arthroplasty, these injuries do occur and their treatment remains challenging. There is a lack of studies reporting on the effectiveness of ceramic components in revision hip arthroplasty after ceramic bearing fracture. The aim of this study is to evaluate clinical and radiologic outcomes of revision surgery with ceramic-on-ceramic components after ceramic bearing fractures in young (i.e., under 60 years old) and active patients. Eight patients who, from May 2004 to November 2011, underwent ceramic-on-ceramic revision surgery following a ceramic component fracture and had more than 6 years follow up were enrolled in this study. All eight patients were male with mean ages at first and revision surgeries of 39 years (range, 31-50 years) and 43.8 years (range, 33-60 years), respectively. There were 6 and 2 cases of ceramic liner and ceramic head fractures, respectively. The average time from the first operation to revision surgery was 54.3 months (range, 9-120 months), and the average follow up period was 9.7 years (range, 6-13.3 years). At the last follow up, all patients showed improvement in Harris hip score and pain relief and there were no cases of loosening or osteolysis. Revision total hip arthroplasty using ceramic-on-ceramic components after ceramic component fracture is a feasible and appropriate surgical option in young and active patients.